The effect of shared service centers on administrative intensity in English local government: A longitudinal evaluation - Elston, T; Dixon, R (Oxford University Press, 2019)
“Administrative intensity” (AI) describes the proportion of total resources that organizations spend on administrative support functions rather than primary service and production processes. We test whether “sharing” administrative activities between organizations leads to a fall in AI due to economies of scale, as is often supposed, using organizational and financial data from more than 300 English local authorities. We employ multi-wave change score regression analysis to relate changes in AI from 2008 to 2016 to levels of shared services participation, and further test whether reform performance varies by category of local authority, type of administration, or degree of structural complexity. Although we find that some measures of AI fell slightly over this period, this was unrelated to shared service adoption for any category of local authority. Sharing of clerical rather than professional types of administration, and sharing by organizations and within partnerships characterized by lower structural complexity, also failed to improve reform outcomes. Faulty assumptions about the extent of administrative scale diseconomies in English local government partly explain this significant reform underperformance.